2013
DOI: 10.1007/s00167-013-2624-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific total knee arthroplasty: the importance of planning by the surgeon

Abstract: Therapeutic study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 22 publications
4
75
0
1
Order By: Relevance
“…The accuracy of the preoperative plan accompanying the PSI was also called into question by our literature review. This represents a significant aspect in procedural efficiency, because four studies demonstrated inaccuracies in anticipated alignment or a need to change the preoperative plan with respect to the planned resections or component sizes [10,27,29,31]. This apparent need for secondary checks would seem to diminish the value of PSI considerably as it relates to operative efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the preoperative plan accompanying the PSI was also called into question by our literature review. This represents a significant aspect in procedural efficiency, because four studies demonstrated inaccuracies in anticipated alignment or a need to change the preoperative plan with respect to the planned resections or component sizes [10,27,29,31]. This apparent need for secondary checks would seem to diminish the value of PSI considerably as it relates to operative efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…One Level II study concluded that the bony cuts achieved using the patient-specific cutting blocks did not always match the preoperative plan generated [29]. An additional Level II study [31] and a Level III study [27] noted a high frequency of intraoperative changes to the preoperative plan and component sizing required to achieve an optimal surgical result. Finally, another Level II study demonstrated that cuts achieved with PSI did not correspond to the preoperative plan when checked intraoperatively with computer-assisted navigation tools [10].…”
Section: Domentioning
confidence: 99%
“…patients [29,37,40,41]. Recently, Woolson et al [40] reported the results of a randomized clinical trial of 22 TKAs performed using a CT-based CCG system ( TKAs performed using standard instrumentation to assess early patient-reported and gait analysis outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, how accurately can the engineer plan a case without relevant clinical information on underlying fixed flexion deformity? The paper of Pietsch et al published in the current issue showed that the surgeon has to revise the planing by the engineer quite regularly [12].There can be a significant mismatch between planning by the engineer and the final component placement. How accurately can the surgeon position guides on flat surfaces like a dysplastic trochlea in the valgus knee?…”
mentioning
confidence: 99%
“…For instance, how accurately can the engineer plan a case without relevant clinical information on underlying fixed flexion deformity? The paper of Pietsch et al published in the current issue showed that the surgeon has to revise the planing by the engineer quite regularly [12].…”
mentioning
confidence: 99%